2021
DOI: 10.1177/08465371211015657
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Association of Radiologists Recommendations for the Safe Use of MRI During Pregnancy

Abstract: The use of magnetic resonance imaging (MRI) during pregnancy is associated with concerns among patients and health professionals with regards to fetal safety. In this work, the Canadian Association of Radiologists (CAR) Working Group on MRI in Pregnancy presents recommendations for the use of MRI in pregnancy, derived from literature review as well as expert panel opinions and discussions. The working group, which consists of academic subspecialty radiologists and obstetrician-gynaecologists, aimed to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 74 publications
(122 reference statements)
0
13
0
1
Order By: Relevance
“…MRI plays a key role in diagnosis and thus far appears to be safe, though its possible side effects are still not ruled out. 11 , 12 A study from Ontario, Canada, 13 revealed that exposure to MRI in the first trimester compared with non-exposure was not associated with an increased risk of harm to the foetus. The theoretical risks of undergoing MRI are biological effects of static and a time-varying magnetic field, the thermal effects associated with radiofrequency exposure and the acoustic noise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MRI plays a key role in diagnosis and thus far appears to be safe, though its possible side effects are still not ruled out. 11 , 12 A study from Ontario, Canada, 13 revealed that exposure to MRI in the first trimester compared with non-exposure was not associated with an increased risk of harm to the foetus. The theoretical risks of undergoing MRI are biological effects of static and a time-varying magnetic field, the thermal effects associated with radiofrequency exposure and the acoustic noise.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no studies demonstrating adverse effects when a pregnant patient is scanned at 1.5 or 3 T in any trimester, but depending on the circumstances, an MRI at 1.5 T or an MRI at 3 T may be recommended. 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the joint American College of Radiology and Society for Pediatric Radiology 2020 practice parameters states that currently available data do not conclusively indicate adverse effects of MRI in pregnancy at either field strength and no special considerations are recommended for any pregnancy trimester and MRI scans may be performed assuming the risk benefit ratio supports the indication 26. In contrast, the Canadian association of radiologist recommend that 1.5 T is preferred if both field strengths are available 27…”
Section: Introductionmentioning
confidence: 99%